DIFFERENCES AND SIMILARITIES BETWEEN KOREAN AND UZBEK SUFFIXES - Mamatqosimova Mashhura (Ta’lim innovatsiyasi va integratsiyasi, 2026)
In today’s globalization process, the comparative study of different languages is considered one of the important directions of linguistics. Especially, studying languages that are structurally similar but belong to different language families is of great scientific importance. The Uzbek language belongs to the Turkic language family, while the Korean language is considered an independent language. Nevertheless, both languages have an agglutinative nature, which is clearly reflected in their grammatical systems. The relevance of this research lies in identifying the similarities and differences between the suffix systems of Korean and Uzbek languages through comparative analysis, thereby facilitating the language learning process and enriching linguistic knowledge. The aim of the study is to determine the functional and structural features of suffixes in Korean and Uzbek languages and to analyze them comparatively.